2006
DOI: 10.1111/j.1439-0426.2006.00711.x
|View full text |Cite
|
Sign up to set email alerts
|

Length-weight relationship of fishes from the Marmara region (NW-Turkey)

Abstract: The relation between length (L) and weight (W) was estimated for 32 species representing 12 families of fishes from six water resources in the Marmara region, Turkey. The parameter b ranged from 2.66 to 3.56. For 12 species length-weight relationships were not previously available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
64
5
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(88 citation statements)
references
References 1 publication
11
64
5
8
Order By: Relevance
“…Our finding was in agreement with the result of Hanel (1991) (see Okgerman et al 2012), Specziár et al (1997), Balık et al (1999), Tarkan et al (2006), Okgerman et al (2012), and Jamali et al (2015). In contrast, Şaşı and Berber (2012) reported that the growth of the white bream population in Uluabat Lake was negative allometric with b value of 2.58.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our finding was in agreement with the result of Hanel (1991) (see Okgerman et al 2012), Specziár et al (1997), Balık et al (1999), Tarkan et al (2006), Okgerman et al (2012), and Jamali et al (2015). In contrast, Şaşı and Berber (2012) reported that the growth of the white bream population in Uluabat Lake was negative allometric with b value of 2.58.…”
Section: Discussionsupporting
confidence: 83%
“…Hamalosmanoğlu (2003) and Okgerman et al (2012) studied the growth and reproductive characteristics in Lake Sapanca. Tarkan et al (2006) reported the length-weight relationship from Lake Sapanca. Şaşı and Berber (2012) examined the age and growth in Uluabat Lake (Bursa Province, Turkey).…”
Section: Introductionmentioning
confidence: 99%
“…Faktor eksternal di antaranya adalah musim, kualitas air, suhu, pH, salinitas, posisi geografis, dan teknik sampling (Jenning et al, 2001). Faktor internal meliputi perkembangan gonad, kebiasaan makan, fase pertumbuhan, dan jenis kelamin (Froese 2006;Tarkan et al, 2006). Rata-rata ukuran pertama kali tertangkap (Lc) lobster bambu (P. versicolor) diperoleh nilai 86 mmCL dengan ukuran matang kelamin (size at 50% ovigerous) pada panjang karapas 88 mm LM.…”
Section: Bahasanunclassified
“…(Hossain et al, 2006), feeding rate, gonadal development and growth phase (Tarkan et al, 2006), behavior (active or passive swimmer) and water flow (Muchlisin et al, 2010).…”
Section: Reproductive Biology Of Fishmentioning
confidence: 99%